13-lined ground squirrel platelets exhibit rod conformation that reduces rates of liver cell phagocytosis - Mancosky, Austin J. (My University, 2019)
Thrombocytopenia, or low levels of platelets in blood, is a symptom of various conditions and is typically treated via platelet transfusions. Donated platelets must be stored at room temperature due to structural damages when chilled, which leads to rapid clearance via liver cells and macrophages post-transfusion. Storage at room temperature leads to a 5-day shelf life, susceptibility to microbial contamination, and limits supply. Hibernating mammals like 13-lined ground squirrels (Ictidomys tridecemlineatus) have platelets that are resistant to cold storage lesions and may reduce phagocytosis. Human and ground squirrel platelets were stored in cold and room temperature, exposed to receptor-glycan-specific enzymes, fluorescently labeled, incubated with HepG2 cells, and HepG2 fluorescence was measured via flow cytometry. Long-term-cold-stored ground squirrel platelets were taken up by HepG2 cells at a significantly slower rate than both control ground squirrel platelets and taxol-treated human platelets (P.<.0.01). Subsequent platelet glycosylation experiments using a FITC-labeled lectin (RCA I) showed that terminal sialic acid residues of ground squirrel platelets remained intact (P > 0.10) while sialic acid was lost in human platelets after cold storage (P < 0.01). Further sequestration and platelet receptor clustering experiments should be performed to better understand how ground squirrel platelets withstand repeated temperature cycles without rapid clearance post-transfusion.
Keywords: Thrombocytopenia; Biology; Ground squirrels